Pemberdayaan Sumber Korporal; Pembelajaran Sejarah di SMA/MA Kota Surakarta - Leo Agung S (LPPM Press, 2011)
This study aims to determine the effectiveness of corporal sources in aneffort to improve the quality of history teaching in senior high schools inAcademic Year 2010/20011 Surakarta. This study uses classroom action researchconducted through two cycles, where each cycle consists of four stages: planning,execution, observation, and refkeksi. This classroom action research aims toimprove the quality of learning history by empowering source of corporal.Subjects were students IPS XI-3 SMA Negeri 6 Surakarta city. Data collectiontechniques and tools used in this study was observational techniques,questionnaires and tests. The results showed that by empowering source ofcorporal to improve the quality of learning history. This is evidenced by the moreactive students in learning and increasing student achievement. In the first cyclestudents' mastery of 70% with an average rating of 68.47, whereas on the secondcycle peningakatan reached 90% with an average rating of 78.05.